Analisis Strategi E-commerce Tokopedia dengan Pendekatan PEST Untuk Penerapan Integrated Marketing Communication (IMC)" - Sucinta Tri Nurhayati; Arfi Andira Kirana; Mira Handani; Nurbaiti . (Jurnal Ekonomi dan Bisnis Digital, 2022)
This study aims to analyze Tokopedia's e-commerce strategy in implementing Integrated Marketing Communication (IMC) by considering the political, economic, social, and technological (PEST) factors. This study employs a qualitative method through a literature review. Tokopedia is one of the 4,444 companies implementing IMC. The research results illustrate the impact of PEST factors on Tokopedia's operations and marketing strategies. Political factors include changes in e-commerce regulations, while economic factors affect product prices and offerings. Social aspects require an approach that understands the culture and ethnic backgrounds of customers. In terms of technology, Tokopedia adopts artificial intelligence and Augmented Reality features. This highlights the importance of adaptability and innovation in the competitive e-commerce business environment. Thus, an IMC strategy that includes PEST factors is crucial for enhancing Tokopedia's success in the e-commerce business in Indonesia.